Transformer Oil Generation and Regeneration Techniques Based on Recent Developments (A Review) - Hassanpour, Malek (International Journal of Petroleum Technology, 2021)
With regard to the wide application of Transformer Oils (TO) as an energy stream on an industrial scale with fast progress towards green TO generation and regeneration technologies, the current review takes into investigation the TO generation industries based on the screening step of industrial projects by Iranian evaluator teams of in-charge organizations. The present review encompassed the TO generation and regeneration technologies from traditional, typical, and recently developed practices in this regard. The technologies extended to introduce green TO generation practices in connection with fossil fuel resources. By the way, a comparison has been done based on technologies posed for TO with the used motor oil reprocessing techniques and used lubricant oil regeneration technologies. To sum up, the current review comprised basic knowledge to select the best technologies for decision-making models in future industrial developments. The prominent achievement of the current review can be mentioned to the aggregation of industrial data for further processing in decision-making theory, criteria, and alternatives selections.